A Qualitative Analysis of the Experiences of People Who Resumed Smoking Following Exclusive Electronic Nicotine Delivery Systems Use. Issue 3 (30th November 2022) - Robertson, Lindsay; Sanford, Kealey-Rei; Waa, Anaru; Hoek, Janet
Abstract: Introduction: For electronic nicotine delivery systems (ENDS) to reduce harms caused by smoking, people who smoke must be able to switch to exclusive ENDS use without subsequently returning to smoking. Identifying factors prompting a return to smoking among former exclusive ENDS users is crucial, yet few qualitative studies have probed experiences of this process. Aims and Methods: We conducted in-depth, semi-structured interviews with 20 people (seven indigenous Māori and 13 non-Māori) who smoked tobacco at least weekly, had smoked at least 100 cigarettes in their lifetime, and reported using ENDS to stop smoking cigarettes for at least 30 days (ideally, within the preceding 6 months). We explored their experiences of ENDS use, probed critical return-to-smoking settings and triggers, and analyzed strategies that could promote sustained smoking abstinence. We managed data using NVivo12 and used a reflexive thematic analysis approach to interpret the transcripts. Results: We identified three themes that explained participants' experiences. ENDS performed a functional role by mimicking some aspects of smoking. Yet participants experienced ENDS as inauthentic and unsatisfying across physical, social, and affectual domains, including in the most common return-to-smoking situations. Furthermore, fewer constraints on ENDS usage led participants to feel they could perpetuate addiction and risk of harm . Conclusions: Return to smoking reflected two factors: ENDS' failure to replicate core smoking attributes that remained appealing, and the burden of self-regulation required when using ENDS. Understanding and informing people about the challenges involved in transitioning to ENDS, beyond obtaining sufficient nicotine, could help support informed ENDS use and may potentially prevent people returning to smoking. Implications: Our study extends our understanding of the satisfaction people seek when attempting to transition from smoking to exclusive ENDS use, and how ENDS' failure to replicate that satisfaction, in addition to uncertainty about ENDS-related risks, contributes to smoking resumption. Satisfaction went beyond nicotine delivery, and included affective experiences, maintenance of rituals, rewards, and social connections. Conceptualizing satisfaction more broadly could support a richer understanding of factors that prompt return to smoking. People might manage challenges more effectively if they understood these before attempting to switch from smoking to ENDS, and if they are advised to monitor and regulate their ENDS use. Educational resources and behavioral support could provide more guidance on these points.